(untitled) (Interdisciplinary Studies Journal, 2026)
This article analyzes the conflict in the Democratic Republic of Congo (DRC), exploring its geopolitical roots, including the Rwandan genocide (1994), the two Congo Wars (1996-1997 and 1998-2003), and the activities of armed groups such as M23, which receives foreign funding. The study, conducted through documentary research, highlights the humanitarian crisis in North Kivu, characterized by extreme violence, forced displacement, and the exploitation of coltan – a mineral crucial for the electronics industry and a central factor in the conflict. It concludes that state fragility and transnational economic interests require a coordinated international response.